A novel loss-of-function mutation of PBK associated with human kidney stone disease - Nettuwakul, Choochai; Sawasdee, Nunghathai; Praditsap, Oranud; Rungroj, Nanyawan; Pasena, Arnat; Dechtawewat, Thanyaporn; Deejai, Nipaporn; Sritippayawan, Suchai; Rojsatapong, Santi; Chaowagul, Wipada; Yenchitsomanus, Pa-thai (Scientific reports, 2020)
Kidney stone disease (KSD) is a prevalent disorder that causes human morbidity worldwide. The etiology of KSD is heterogeneous, ranging from monogenic defect to complex interaction between genetic and environmental factors. Since mutations of genes responsible for KSD in a majority of families are still unknown, our group is identifying mutations of these genes by means of genomic and genetic analyses. In this study, we identified a novel loss-of-function mutation of PBK , encoding the PDZ binding kinase, that was found to be associated with KSD in an affected Thai family. Glycine (Gly) substituted by arginine (Arg) at position 43 (p.Gly43Arg) in PBK cosegregated with the disease in affected members of this family, but was absent in 180 normal control subjects from the same local population. Gly43 is highly evolutionarily conserved in vertebrates, and its substitution affects protein structure by alterations in H-bond forming patterns. This p.Gly43Arg substitution results in instability of the variant PBK protein as examined in HEK293T cells. The variant PBK protein (p.Gly43Arg) demonstrated decreased kinase activity to phosphorylate p38 MAPK as analyzed by immunoblotting and antibody microarray techniques. Taken together, these findings suggest a possible new mechanism of KSD associated with pathogenic PBK variation.